The Role of Leadership, Collaboration, and Integrity in Running a Student Organization - Yuliantini Yuliantini; Aang Gunawan; Olfebri Olfebri; Lira Agusinta (Siber Nusantara of Community Service Review, 2026)
Leadership and integrity are two fundamental factors that determine the success of student organization management. However, various challenges remain common in student organizations, including low member participation, ineffective communication, weak commitment to organizational programs, and limited understanding of the importance of integrity in carrying out organizational responsibilities. This community service activity aimed to enhance students’ understanding and awareness of the role of leadership and integrity in managing student organizations. The program was conducted offline at Institut Transportasi dan Logistik Trisakti in June 2026 and involved approximately 50 students from various academic programs and student organizations. The methods employed included lectures, structured and systematic motivational sessions, interactive discussions, case studies, and program evaluations. The results indicated an improvement in participants’ understanding of leadership concepts, the importance of integrity, and their implementation in organizational management. Participants recognized that leadership is not merely associated with formal positions but also with the ability to influence, inspire, and mobilize organizational members toward common goals. Furthermore, integrity was understood as a fundamental value for building trust, responsibility, accountability, and professionalism within organizations. The activity had a positive impact on increasing students’ awareness and commitment to applying leadership and integrity values in organizational activities. Therefore, similar programs should be implemented continuously to support the development of professional, accountable, and goal-oriented student organizations.